Інкотермс 2010 в зовнішньоекономічній діяльності будівельних підприємств України - Зельцер, Р. Я.; Ізотов, К. О. (Ways to Improve Construction Efficiency, 2012)
The article reviews the main innovations of Incoterms 2010. The possibilities to use thenew edition of rules in supply contracts of Ukrainian construction enterprises have been revealed.